Climate analogues: finding tomorrow’s climate adaptation solutions today - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
It is no great secret that climate change presents a massive challenge to agriculture. While some regions will develop a climate that favours agriculture, most will not. Even in places where conditions improve, many resource-poor smallholders will be hard pressed to take advantage of the additional production potential while, in areas where conditions deteriorate, farmers will have to adapt to their new circumstances as quickly as possible. This will be particularly difficult for smallholders who completely depend on agriculture for their food and livelihoods. Strategies and technologies for adapting to climate change in particular locations should ideally be grounded in knowledge of the future climatic conditions in those locations. Estimates hold that 70% of future climates already exist somewhere in the world. That is where the analogues approach comes in.